AB072. Efficacy and safety of 120-W GreenLight High Performance System photoselective vaporization of the prostate: 5-year results - Park, Juhyun (Transl Androl Urol, 2016)
OBJECTIVE: To investigate 5-year postoperative results of photoselective vaporization of the prostate using the 120-W GreenLight High Performance System photoselective vaporization of the prostate (HPS-PVP) for treating benign prostate hyperplasia METHODS: A total 208 men who underwent HPS-PVP and were followed up for five years were analyzed retrospectively. Surgical outcomes were assessed by the ratio of the IPSS/QoL, the difference in Qmax/PVR and the difference of the prostate volume by transrectal ultrasonography before surgery and at 6, 12, 36 and 60 months postoperatively. The presence of postoperative complications was verified at every follow-up visit. RESULTS: Preoperative parameters such as mean age, prostate volume, IPSS, QoL, Qmax and PVR, were 67.9±8.2 years, 48.4±26.3 mL, 20.4±8.7, 4.0±9.2±3.5 mL/s, and 81.3±92.0 mL, respectively. Perioperatively, mean operative time, lasing time, used energy, and postoperative urethral catheter indwelling time were 67.4±45.9 minutes, 26.7±29.3 minutes, 89.6±82.5 kJ and 24.5±11.0 hours, separately. There were significant improvements in all outcome measures after 3, 12, 36 and 60 months. Forty-nine (23.6%) patients had immediate postoperative complications which were managed successfully nonsurgical methods. There were no transfusion cases. A single case (1.5%) showed mild urethral stricture with voiding difficulty 12 months postoperatively and required urethral dilation using panendoscopy. CONCLUSIONS: HPS-PVP is an effective and safe procedure for treating benign prostatic hyperplasia.